Pengaruh Kepemimpinan dan Disiplin Kerja terhadap Kinerja Karyawan PT. Indah Logistik Cargo Cabang Pematangsiantar - Melati Siregar, Lamria Rini; Sibagariang, Susy Alestriani; Simamora, Benjamin Albert (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
This study aims to determine whether there is a significant influence between leadership and work discipline on PT employees' performance. Indah Logistik Cargo Pematangsiantar Branch, either partially or simultaneously. The method used is descriptive quantitative with a sample of 30 respondents data collection techniques using questionnaires and documentation. The data obtained were analyzed using multiple linear regression. The research results are that leadership and work discipline positively and significantly affect employee performance with the regression equation Y = 38.737 + 0.095 X1 + 0.149 X2 + e. Hypothesis testing is obtained if the calculated F value > F table or (3.412 > 3.34). It is also strengthened by a significant probability of 0.048 < 0.05. Thus H0 is rejected, and H3 is accepted. This means that there is a significant influence simultaneously and partially between leadership and work discipline on PT employees' performance. Indah Logistics Cargo Pematangsiantar Branch.